One-pot synthesis of cyclic oligosaccharides by the polyglycosylation of monothioglycosides. (January 2020) - Someya, Hidehisa; Seki, Takehito; Ishigami, Gota; Itoh, Taiki; Saga, Yutaka; Yamada, Yasuyuki; Aoki, Shin
Abstract: Cyclic oligosaccharides such as cyclodextrins (CyDs) have been known as excellent host molecules for the inclusion of various organic guest molecules. The development of new synthetic methods for preparing cyclic oligosaccharides from simple and readily available glycosyl donors would be highly desirable, since the current traditional synthetic routes include multiple reaction steps (glycosylation reactions and deprotections). We herein report on the synthesis of cyclic oligosaccharides by polyglycosylation of monothioglycosides, typically, 2, 3, 4-protected 1-thioglycosides. A series of promoters and solvents were tested for the glycosylation of thiogalactosides that contain a hydroxy group at the 6-position, and glycosylation using a N -iodosuccinimide (NIS)/trimethylsilyl triflate (TMSOTf) promoter system in dichloromethane afforded cyclic oligosaccharides which consist of tri~penta galactosides containing repeating β-(1→6) glycosidic linkage as major products, as evidenced by a single crystal X-ray structure analysis of the cyclic tetragalactoside. The effect of reaction temperature and reactant concentrations on the glycosylation products was also investigated. The cyclic glucosides were obtained by the glycosylation of the thioglucosides. Moreover, protecting groups of the synthesized cyclic tetragalactoside were removed to obtain deprotected cyclic tetragalactoside. Graphical abstract: Image 1 Highlights: Cyclic oligogalactosides & cyclic oligoglucosides were synthesized by polyglycosylation of corresponding monothioglycosides. N -Iodosuccinimide/trimethylsilyl triflate promoter system gave cyclic oligosaccharides in acceptable chemical yields. The structure of cyclic tetragalactoside was determined by a single crystal X-ray structure analysis.